Effect of Twisted-Tape Turbulators and Nanofluid on Heat Transfer in a Double Pipe Heat Exchanger - Heydar Maddah; Reza Aghayari; Morshed Farokhi; Shabnam Jahanizadeh; Khatere Ashtary (Journal of Engineering)
Heat transfer and overall heat transfer in a double pipe heat exchanger fitted with twisted-tape elements and titanium dioxide nanofluid were studied experimentally. The inner and outer diameters of the inner tube were 8 and 16 mm, respectively, and cold and hot water were used as working fluids in shell side and tube side. The twisted tapes were made from aluminum sheet with tape thickness (d) of 1 mm, width (W) of 5 mm, and length of 120 cm. Titanium dioxide nanoparticles with a diameter of 30 nm and a volume concentration of 0.01% (v/v) were prepared. The effects of temperature, mass flow rate, and concentration of nanoparticles on the overall heat transfer coefficient, heat transfer changes in the turbulent flow regime Re≥2300, and counter current flow were investigated. When using twisted tape and nanofluid, heat transfer coefficient was about 10 to 25 percent higher than when they were not used. It was also observed that the heat transfer coefficient increases with operating temperature and mass flow rate. The experimental results also showed that 0.01% TiO2/water nanofluid with twisted tape has slightly higher friction factor and pressure drop when compared to 0.01% TiO2/water nanofluid without twisted tape. The empirical correlations proposed for friction factor are in good agreement with the experimental data.